Could hypoxic conditioning augment the potential of mesenchymal stromal cell-derived extracellular vesicles as a treatment for type 1 diabetes? - Cathal Patrick Forkan; Aruna Shrestha; Alfred Yu; Christine Chuang; Flemming Pociot; Reza Yarani (Stem Cell Research & Therapy)
Abstract Type1 Diabetes (T1D) is an autoimmune disorder characterised by the loss of pancreatic β-cells. This β cell loss occurs primarily through inflammatory pathways culminating in apoptosis. Mesenchymal stromal cells (MSCs) have been heavily studied for therapeutic applications due to their regenerative, anti-apoptotic, immunomodulatory, and anti-inflammatory properties. The therapeutic effects of MSCs are mediated through cell-to-cell contact, differentiation, and the release of paracrine factors, which include the release of extracellular vesicles (EVs). Culturing MSCs in hypoxia, a low oxygen tension state more analogous to their physiological environment, seems to increase the therapeutic efficacy of MSC cell therapy, enhancing their immunomodulatory, anti-inflammatory, and anti-fibrotic properties. This is also the case with MSC-derived EVs, which show altered properties based on the parent cell preconditioning. In this review, we examine the evidence supporting the potential application of hypoxic preconditioning in strengthening MSC-EVs for treating the inflammatory and apoptotic causes of β cell loss in T1D.